Wear mechanism of TC4 titanium alloy with TiN coating against self-lubricating fabric - Zhao, Song; Zhang, Haoran; Qi, Xiaowen; Dong, Yu; Zhang, Yan (MDPI AG, 2023)
Vapor deposition technology can improve the surface wear resistance of titanium alloys, and prepare lightweight and corrosion-resistant self-lubricating spherical plain bearings made of titanium alloys. However, titanium alloys with hard films can be worn by soft self-lubricating fabrics. This paper focuses on the wear problem of TiN coating on the surfaces of self-lubricating spherical plain bearings based on titanium alloys. Ring-to-plate wear tests were carried out to study the tribological properties of TiN coating on TC4 titanium alloy against self-lubricating fabric under different working conditions (load: 500–2000 N and speed: 100–500 r/min), along with the investigation of the wear mechanism of TiN coating, and the evaluation of applicable working conditions of GE15 type self-lubricating spherical plain bearings through swing tests. The results have revealed that TiN coatings can maintain a certain friction distance without wear. Increasing friction speed and load can make TiN coatings more prone to wear. A thick transfer film can protect the TiN coating from wear. The main wear mechanism is attributed to fatigue wear induced by the repeated formation and peeling of transfer films. The GE15 bearing has achieved a self-lubricating fabric wear of approximately 0.04 mm when the swinging for 500 m (25,000 times) is under a specific condition of 27 kN and 0.2 Hz without damaging the inner ring of the bearing. The bearing is suitable for swing conditions with applied loads below 27 kN. This study provides a fundamental understanding of designing self-lubricating spherical plain bearings made of titanium alloys.